Arterial Ultrasound Testing to Predict Atherosclerotic Cardiovascular Events - Nicolaides, Andrew N.; Panayiotou, Andrie G.; Griffin, Maura B.; Tyllis, Theodosis; Bond, Dawn; Georgiou, Niki; Kyriacou, Efthyvoulos C.; Avraamides, Costantinos; Martin, Richard M. (My University, 2022)
Studies have indicated that the presence and size of subclinical atherosclerotic plaques improve the prediction of atherosclerotic cardiovascular events (ASCVE) over and above that provided by conventional risk factors alone. However, the relative contribution of different ultrasonographic measurements and sites of measurements on the 10-year ASCVD risk is largely unknown.
Keywords: Carotid plaque; Common femoral plaque; Subclinical atherosclerosis; Total plaque thickness; Ultrasound